2008
DOI: 10.1016/j.ejheart.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular solid body rotation in non‐compaction cardiomyopathy: A potential new objective and quantitative functional diagnostic criterion?

Abstract: Background: Left ventricular (LV) twist originates from the interaction between myocardial fibre helices that are formed during the formation of compact myocardium in the final stages of the development of myocardial architecture. Since non-compaction cardiomyopathy (NCCM) is probably caused by intrauterine arrest of this final stage, it may be anticipated that LV twist characteristics are altered in NCCM patients, beyond that seen in patients with impaired LV function and normal compaction. Aims: The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 31 publications
8
87
0
9
Order By: Relevance
“…В экспериментальных работах на собаках было по-казано, что снижение апикального вращения про-исходит параллельно снижению деформации апи-кальных сегментов. При этом апикальная ротация по-степенно снижается и затем становится обратной, пас-сивно следуя за вращением базальных отделов [1,3,26]. Это положение также было продемонстрировано в нашем исследовании.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…В экспериментальных работах на собаках было по-казано, что снижение апикального вращения про-исходит параллельно снижению деформации апи-кальных сегментов. При этом апикальная ротация по-степенно снижается и затем становится обратной, пас-сивно следуя за вращением базальных отделов [1,3,26]. Это положение также было продемонстрировано в нашем исследовании.…”
Section: Discussionunclassified
“…Спиральное строение миокарда, описанное Torrent-Guasp как непрерывная мышечная лента, играет важную роль в физиологии кардиального сокращения [1]. Подобная уникальная пространственная конфигу-рация миокарда обеспечивает анатомическую основу для максимально эффективной работы левого желу-дочка (ЛЖ).…”
Section: Diastolic Function Of the Left Ventricle In Cardiomyopathiesunclassified
“…A speckle tracking study in 10 patients with dilated cardiomyopathy and 10 patients with non-compaction cardiomyopathy by Van Dalen et al [21] also reported about the occurrence of rigid body rotation. In both patient groups, 3 people had an electrical conduction delay (bundle branch block).…”
Section: Rigid Body Rotationmentioning
confidence: 99%
“…were the first to demonstrate that 2DSTE-derived 'LV solid/rigid body rotation', with near absent LV twist, may be a new sensitive and specific, objective and quantitative, functional diagnostic criterion and have good predictive value for the diagnosis of NCCM (55,56). LV myocardial deformation was also found to be reduced in the longitudinal and circumferential dimensions and manifested tight systolic-diastolic coupling in children with NCCM (57).…”
Section: Alternative Ways To Assess Left Atrial Function In Noncompacmentioning
confidence: 97%